Attributional triadic relationships between end-users, specifiers, and vendors: evidence from building supply retailers - Palomino-Tamayo,Walter (2022)
Purpose: This study proposes to evaluate product attributes in an unusual triad of actors: end-users, vendors, and specifiers. The differences in perceptions of product attributes between these triadic actors can bias strategic marketing decisions for functional and aesthetic products in a building supply retailer, which is understudied in the retail literature. Theoretical framework: The study uses the attribution theory approach and provides a new perspective to explain differences in attribute evaluations in this triad (end user-specifier-vendor). Design/methodology/approach: The hypotheses are tested in two countries' functional and aesthetic building material categories. Attribute evaluations were performed using the ranking method and Borda count. We used ANOVA, linear discriminant analysis (LDA), and the Mahalanobis squared distance (MSD) for the estimations. Findings: The hypothesis tests confirmed the difference in attribute evaluations between end-users, vendors, and specifiers for functional products; however, as we hypothesized, no difference was found for aesthetic products. Practical & social implications of research: Our discussion will help retail practitioners avoid bias in marketing strategy. In the development of new products, manufacturing companies should consider differences between actors, especially in collaborative product developments. Originality/value: This study contributes to the literature by using an attribution theory approach and provides a new perspective to explain differences in attribute evaluations in this triad (end-user-specifier-vendor). We provide insights into allocating causes and responsibility in product attribute selection.